AGRONOMIC EFFICIENCY OF THE INTERCROPPING LETTUCE-ARUGULA FERTILIZED WITH ROOSTERTREE - Almeida, Antonio Ewerton da Silva (2015)
The present work aimed to evaluate the agronomic performance of lettuce-arugula intercropping fertilized with different amounts of roostertree biomass incorporated into the ground. The experiment was conducted during the period of September to November of 2011, in the research area of the Experimental Farm Rafael Fernandes, Universidade Federal Rural do Semi-Árido, Mossoró-RN. The experimental design used was randomized blocks with five treatments and four replications. The treatments consisted of the following biomass amounts of roostertree incorporated into the soil (5, 15, 25, 35, and 45 t ha- 1 on a dry basis). The characteristics evaluated in the vegetables were: height and diameter of plants (lettuce), number of leaves per plant, productivity (lettuce), yield of green mass (arugula) and dry mass of shoots. The efficiency of intercropping system was determined through the score of the canonical variable. The optimization of the agronomic performance of the lettuce intercropped with arugula was made possible with the incorporation of about 37 t ha-1 of roostertree into the ground. The use of roostertree as green manure is agronomically viable in the intercropping of lettuce and arugula besides contributing to a better use of environmental resources.